Research on operation strategy of the Central Sterile Supply Department from the perspective of cost management (基于成本管理视角的医院消毒供应中心运营策略研究) - ZHANG Ying (张颖); GU Qin (顾琴); TANG Huiqiong (汤会琼) (Association of Integrative Nursing, 2022)
Objective　Methods cost accounting methods for operation cost of CSSD was conducted based on activity-based costing theory. Unit costs of services from recycling of disinfection sterilization package, cleaning and disinfection, high and low temperature sterilization were calculated precisely. Calculation of unit cost was standardized and refined. Results In the information tracing management system, the calculating formula was generated to perform the cost statistics monthly. Labor costs accounted for the highest proportion in each process of CSSD. Conclusion Scientific cost management can provide an important basis for managers to scientifically manage the cost of CSSD for internal transfer pricing and external service pricing strategies . A study on　To improve the cost accounting of hospital Central Sterile Supply Department (CSSD), explore the operation decision of CSSD based on cost management perspective, and study the cost accounting method of disinfection supply service in line with the actual situation of the hospital. (目的 完善医院消毒供应中心成本核算方法, 探讨基于成本管理视角的消毒供应中心运营决策, 研究符合医院实际情况的消毒供应服务成本核算方式。方法 基于作业成本法理论对医院消毒供应服务成本核算方式开展进一步研究, 通过划分测算业务流程成本, 精准计算消毒灭菌包回收发放、接分清洗消毒、检查保养包装、高低温灭菌的单位成本, 将每个消毒灭菌包单位成本计算方式标准化、精准化。结果 信息追溯管理系统内设计消毒灭菌包的计算公式, 每月进行费用成本计算统计和汇总。各流程中, 人力成本占比最高。结论 科学的成本管理, 对消毒供应服务内部转移定价和外部服务定价策略有利于管理者为科学地做好消毒供应中心成本计划和精细化管理提供重要依据。)